2017
DOI: 10.1016/j.celrep.2017.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Drives Distinct Projection Neurons in the Basolateral Amygdala

Abstract: SUMMARY The prefrontal cortex (PFC) regulates emotional behavior via top-down control of the basolateral amygdala (BLA). However, the influence of PFC inputs on the different projection pathways within the BLA remains largely unexplored. Here we combine whole-cell recordings and optogenetics to study these cell-type specific connections in the mouse BLA. We characterize PFC inputs onto three distinct populations of BLA neurons that project to either the PFC, ventral hippocampus or Nucleus Accumbens. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 45 publications
9
82
0
Order By: Relevance
“…The addition of 4-AP and subsequent blockade of voltage-gated potassium channels induced additional depolarization at the terminals so that ChR2-mediated depolarization was then enough to trigger glutamate release (Figure 1). Our results are consistent with the monosynaptic nature of the mPFC -BLA projections that has demonstrated previously by others (Arruda-Carvalho and Clem, 2014;Cho et al, 2013;Kiritoshi and Neugebauer, 2018;Little and Carter, 2013;McGarry and Carter, 2017). Importantly, we compared paired-pulse ratios recorded in the presence of TTX and 4-AP as well as under standard conditions and we did not observe a significant difference, suggesting that our recordings did not contain significant polysynaptic contributions to our glutamatergic recordings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The addition of 4-AP and subsequent blockade of voltage-gated potassium channels induced additional depolarization at the terminals so that ChR2-mediated depolarization was then enough to trigger glutamate release (Figure 1). Our results are consistent with the monosynaptic nature of the mPFC -BLA projections that has demonstrated previously by others (Arruda-Carvalho and Clem, 2014;Cho et al, 2013;Kiritoshi and Neugebauer, 2018;Little and Carter, 2013;McGarry and Carter, 2017). Importantly, we compared paired-pulse ratios recorded in the presence of TTX and 4-AP as well as under standard conditions and we did not observe a significant difference, suggesting that our recordings did not contain significant polysynaptic contributions to our glutamatergic recordings.…”
Section: Discussionsupporting
confidence: 92%
“…withdrawal from chronic ethanol exposure may cause the IL/vmPFC terminals to engage with a different population of neurons or the amount of stimulation we had to apply to these terminals to elicit comparable EPSCs in the AIR and CIE/WD animals may have been different, resulting in greater stimulation and GABAergic release in our withdrawal recordings. The latter hypothesis is feasible considering the fact that the prefrontal cortex has been shown the drive distinct populations of projection neurons in the BLA (Laura McGarry et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we measured light-evoked input-specific quantal EPSCs (qoEPSCs) by replacing our intracellular medium’s calcium with strontium to desynchronize transmitter release (Figure 5) (Britt et al, 2012; McGarry and Carter, 2017). qoEPSCs amplitude provide a direct estimate of postsynaptic efficacy measure and qoEPSC frequency was taken as an indirect indication of the number of connections (Goda and Stevens, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated segregation of projection defined cell types in the mouse BLA 20,21 . Genetically distinct BLA cell populations with unique functional and connectional phenotypes also have been identified 22 .…”
Section: Introductionmentioning
confidence: 99%